Spatial skills of preschool children from Serbia and a possible model for the typology of children’s spatial skills - Đokić, Olivera J.; Vorkapić, Marija M. (Frontiers in Education, 2024)
The authors of the paper focus on the impact of the curriculum on the development of the preschool children's spatial abilities and an important aspect of children's understanding of space through Piaget's primacy of topological concepts and an increasing turn to projective geometry. The aim of the research is to examine spatial abilities of preschool children in Serbia in the year before they enroll at primary school (age 5.56.5). The research involved 103 children who were exposed to two different preschool curricula: The General Foundations of the Preschool Curriculum (GFPC) and The Foundations of the Preschool Curriculum -Years of Ascent (YA). By interviewing each child individually in a structured interview, we obtained results that show that children solved the tasks poorly, so we continue to search for other models for the typology of children's spatial skills in relation to the typology of the 2×2 matrix (Newcombe, 2018) that we used. We open the question of a model that would better describe the development of spatial abilities of preschool children in Serbia and could serve the creators of the curriculum for its enrichment in terms of development of children's spatial reasoning as essential for success in STEM fields as shown by meta-analyses of children's spatial abilities.